Model lipid bilayers as sensor bionanomaterials for characterization of membranotropic action of water-soluble substances - Vashchenko, O.V.; Kasian, N.A.; Brodskii, R.Ye.; Budianska, L.V.; Sofronov, D.S.; Lisetski, L.N. (Functional Materials, 2018)
Model phospholipid membranes are considered as sensor bionanomaterials to characterize water-soluble drugs of kosmotropic and chaotropic nature. Effects of kosmotropic agent dimethylsulfoxide (DMSO) and chaotropic tilorone on 1,2-dipalmitoylphosphatidylchoine multibilayer membranes were studied by differential scanning calorimetry and Fourier-transformed infrared spectroscopy. Tilorone and DMSO, water soluble hydrophilic substances, induced opposite shifts of membrane main phase transition temperatures ΔT, which were positive for DMSO (as a kosmotropic dopant) and negative for chaotropic tilorone. For both dopants, dependences of ΔT vs. dopant concentration c were obtained and fitted by an analogue of the Freundlich equation of adsorption, ΔT = kc¹/n. A model has been proposed describing the action of hydrophilic dopants on lipid bilayer in terms of additional lateral pressure P(c), which is positive for kosmotropes and negative for chaotropes. Applying the Clapeyron-Clausius equation to establish the character of ΔT(c) relation, power-law dependence was obtained, which was in good agreement with our exrimental data. From comparison with literature data on Langmuir monolayers of similar systems, it was noted that the same power law relations could describe both phase transition temperature shifts and pressure-area dependences as function of dopant concentration.